Evaluation of reliable improvement rates in depression and anxiety at the end of treatment in adolescents - Edbrooke-Childs, J; Wolpert, M; Zamperoni, V; Napoleone, E; Bear, H (Cambridge University Press, 2018)
Background Literature has focused on effect sizes rather than individual-level improvement rates to determine how effectively services address burgeoning numbers of adolescents with anxiety and depression.